A Review of Defending Frequently Challenged Young Adult Books, Teaching Banned Books, and Books Under Fire - Terri Suico (University of Oklahoma Libraries, 2023)
This in-depth review of three of Pat R. Scales' books provides summaries of the books as well as insight regarding their value for educators and librarians given the current issues surrounding censorship.